Impact of the COVID-19 Pandemic and Public Restrictions on Outcomes After Catheter Ablation of Atrial Fibrillation - Kim, Daehoon; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Background Here we aimed to analyze changes in the outcomes of atrial fibrillation (AF) catheter ablation (AFCA) during the coronavirus disease 2019 (COVID-19) pandemic and examine the relationship between rhythm outcomes and the stringency of government social distancing measures. Methods We included 453 patients who underwent de novo AFCA between May 2018 and October 2019 (pre-COVID-19 era) and 601 between November 2019 and April 2021 (COVID-19 era). The primary outcome was late recurrence, defined as any episode of AF or atrial tachycardia documented after a 3-month blanking period. A multivariable Cox regression analysis was performed to estimate the relative hazards of AF recurrence in the two eras. Results In the study population (24.3% women; median age, 60 years), 660 (62.6%) patients had paroxysmal AF. Among those with paroxysmal AF, the late recurrence rate was significantly lower in the COVID-19 era than in the pre-COVID-19 era [9.4% vs. 17.0%, respectively, log-rank P = 0.004; adjusted hazard ratio (HR) 0.56, 95% confidence interval (CI) 0.35–0.90] during a median follow-up of 11 months. In patients with persistent AF, the late recurrence rate did not significantly differ between the pre-COVID-19 and COVID-19 era groups (18.9% vs. 21.5%, respectively; log-rank P = 0.523; adjusted HR 0.84, 95% CI 0.47–1.53) during the median follow-up of 11 months. Conclusion A decrease in AF recurrence after catheter ablation was observed in patients with paroxysmal AF during the COVID-19 outbreak, whereas no change was observed in those with persistent AF.